Batch and continuous cultivation processes of Candida tropicalis TISTR 5306 for ethanol and pyruvate decarboxylase production in fresh longan juice with optimal carbon to nitrogen molar ratio. (16th August 2019) - Nunta, Rojarej; Techapun, Charin; Jantanasakulwong, Kittisak; Chaiyaso, Thanongsak; Seesuriyachan, Phisit; Khemacheewakul, Julaluk; Mahakuntha, Chatchadaporn; Porninta, Kritsadaporn; Sommanee, Sumeth; Trinh, Ngoc T.; Leksawasdi, Noppol
Abstract: The carbon to nitrogen (C/N) molar ratio of 21.88 ± 0.20 in fresh juice from C‐grade longan (FLJ‐C) supplemented with ammonium sulfate (AMS) was optimal for cultivation of Candida tropicalis TISTR 5306 producing ethanol concentration of 24.0 ± 1.1 g/L and specific pyruvate decarboxylase (PDC) activity of 0.138 ± 0.001 U/mg protein. The highest ethanol concentration in a 10 L continuous process (34.3 ± 0.5 g/L, dilution rate [ D ] = 0.0492 hr −1 ) was significantly higher ( p  ≤ .05) than that in 100 L batch process (13.2 ± 0.2 g/L at 108 hr). The highest volumetric PDC activities of 0.081 ± 0.001 U/ml ( D = 0.0070 hr −1 ) and 0.107 ± 0.001 U/ml (48 hr) were attained for continuous and batch processes, respectively. The affinity constants and growth‐related weighting factors on sucrose and monosaccharides (glucose and fructose with the same values) utilization were (123 ± 1 g/L, 0.14 ± 0.01) and (34.1 ± 1.5 g/L, 0.43 ± 0.01) with MS and R 2 of 92.2 and .9552, respectively. Practical applications: FLJ‐C is an example of agricultural produces with relatively high production quantity (50, 000 t/year in Thailand) and high sugars content but low marketing demands due to the smallest size of pulp. The complex nitrogen source contains costly components (yeast extract—78.3 USD/kg, malt extract—148 USD/kg, and peptone—151 USD/kg) which can be replaced with an inexpensive AMS (1.05 USD/kg). Further consideration of C/N molar ratio in FLJ‐C can optimize growth, ethanol (alternative biofuel/industrial solvent) production, and specific PDC (biocatalyst for phenylacetylcarbinol—PAC, anti‐asthmatic and nasal decongestant precursors) activity of C. tropicalis TISTR 5306 whole cells which can be used as a case study for other related yeasts. Batch and continuous production at 100 L and 10 L also illustrate practical utilization of FLJ‐C with AMS supplement at larger scales for development of subsequent zero waste process.